A spontaneous reduction in tumor size of a thymic carcinoma: a case report - Shoei Kuroki; Takanori Ayabe; Hiroyuki Tanaka; Hiroshi Nakada; Ryo Maeda (Surgical Case Reports, 2022)
Abstract Background Spontaneous regression of thymic carcinoma is extremely rare. We report a case of a resected thymic carcinoma with preoperative spontaneous regression in a 67-year-old woman. Case presentation The patient presented with low-grade fever and anterior chest pain. Chest computed tomography (CT) showed a 55 × 43 mm exophytic heterogeneously enhancing mass showing some areas of necrosis. Chest CT done one day preoperatively revealed that the tumor had rapidly shrunk for one month. Surgical resection was performed to obtain a definitive diagnosis and achieve complete resection, yielding a postoperative diagnosis of thymic carcinoma. The patient survived without signs of recurrence for 12 months postoperatively. Conclusions Mediastinal tumors with necrosis demonstrating spontaneous regression should include thymic carcinomas in the differential diagnosis.